A 2500-YR-LONG PALEOSEISMOLOGIC RECORD OF LARGE, INFREQUENT EARTHQUAKES ON THE NORTH ANATOLIAN FAULT AT ÇUKURçIMEN, TURKEY - Hartleb R.D.; Dolan J.F.; Kozaci Ö.; Akyüs H.S.; Seitz G.G. (My University, 2006)
Paleoseismologic trenches excavated across the North Anatolian fault near the village of Çukurçimen in north-central Turkey yield a complete record of surface ruptures for the past 2500 yr. The trenches provide mutually consistent evidence for the timing of the five most recent surface ruptures at the site, as well as at least two older events. These are interpreted as: (1) the historic 1939 Mw 7.9 earthquake; (2) the historic 1254 A.D. earthquake; (3) the historic 1045 A.D. earthquake; (4) an earthquake that probably occurred late in the interval between 250 and 540 A.D., possibly the historic 499 A.D. earthquake; and (5) an earthquake that occurred sometime between 770 and 50 B.C. (and probably between 230 and 50 B.C.). One additional earthquake occurred sometime between 1450 and 800 B.C., and at least one other surface rupture occurred between 2880 and 200 B.C., but the stratigraphic section at the site was not completely exposed for sediments older than ~2500 yr. As a result, it is unclear whether the oldest event horizons represent a single earthquake, or multiple events. Our findings, when coupled with other published results and the historical record, enable us to construct a space-time history of earthquakes along the North Anatolian fault. The most striking aspects of this analysis are: (1) the rarity of earthquakes at any given place along the fault, suggesting that the fault typically ruptures in large, infrequent events; (2) earthquake occurrence is relatively temporally regular, with inter-event times that range from ~200 to <900 yr, and vary by a factor of only 3-4; and (3) almost the entire length of the North Anatolian fault ruptured in short-lived clusters of activity in the seventeenth to eighteenth centuries and in the tenth to twelfth centuries, similar to the twentieth-century sequence. The magnitude and sequence of the individual ruptures, however, have varied considerably between clusters. Moreover, the paleoseismologic and historical data indicate that the North Anatolian fault does not always rupture in sequences similar to the twentieth-century cluster. These results suggest that the relatively regular recurrence of rare, large-magnitude earthquakes may be the expected mode of earthquake occurrence on mature strike-slip faults in settings where such faults are structurally isolated from other major seismic sources. © 2006 Geological Society of America.
Keywords: ACTIVE TECTONICS; EARTHQUAKE OCCURRENCE; NORTH ANATOLIAN FAULT; PALEOSEISMOLOGY; SAN ANDREAS FAULT